INTERNET WEBPAGE AS A TOOL FOR CREATING COMPETITIVENESS IN AGRITOURISM - Kosmaczewska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2010)
The purpose of this article is an attempt to reply to the question if agritourism farms in Wielkopolskie Province use their webpages as a tool for creating their competitiveness. For that reason, 112 farms were examined, 75 of them kept their own webpages and 37 of them only had a generally accessible e-mail account. The study consisted in the assessment of replies obtained to the booking enquiry sent via e-mail to the farms under study. Content of the webpages was subject to an analysis. On the basis of the results of the study it may be concluded that too few of the farms view their webpages as a tool for creating the competitive advantage. Own webpage is most often seen by the farms as a pretty cheap advertising tool but not as a distribution channel with vast potential increase.